The Effect of Competence of Conservative Dentist Specialists on Patient Satisfaction with Dental Health Services and Its Relationship to BPJS Patient Loyalty at the Hospital - Jeanny Kathleen Hartini; Kosasih Kosasih (CV. Publikasi Indonesia, 2024)
This study examines the influence of the competence of dental conservation specialists on patient satisfaction and its relationship to BPJS patient loyalty in hospitals. The competencies of dental specialists, including technical expertise, deep knowledge, and communication skills, are crucial in delivering high-quality and satisfying dental health services. Patient satisfaction is a key indicator of healthcare success, especially in dental services, where procedures such as root canal therapy and dental restoration require a high level of expertise. This research aims to analyze how the competence of dental conservation specialists impacts patient satisfaction and how this satisfaction influences BPJS patient loyalty. The research utilizes a qualitative approach with a case study method involving BPJS patients who received dental conservation services in hospitals. Data were collected through semi-structured interviews and questionnaires, focusing on patients' experiences with dental services. The data were analyzed using thematic analysis, identifying key themes related to dentist competence, patient satisfaction, and loyalty. The findings highlight the importance of continuous training for dental conservation specialists in improving patient satisfaction and fostering loyalty to the hospital's services. These efforts will not only enhance the quality of dental care but also support the sustainability of the BPJS program in providing accessible and affordable healthcare.